2014
DOI: 10.7567/jjap.53.058006
|View full text |Cite
|
Sign up to set email alerts
|

First-principles evaluation of penetration energy of metal atom into Si substrate

Abstract: The difference in chemical potential between bulk metal and bulk Si was calculated for various metal atoms using the first-principles calculations. It was shown that such a difference is an adequate measure for the penetration energy of a metal atom from a metal/Si interface into a Si substrate and important in understanding the phenomena around metal/Si interfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…Using these values, for example, we can estimate the vacancy density in bulk layers as 10 10 cm -3 , which is in good agreement with recent experiments [4]. These formation energies in inner bulk layers mainly originate from the elastic energy loss produced by the insertion of foreign atoms in bulk crystal structure [5]. It is noted here that the formation energy decreases as the point defect approach the interface.…”
Section: Resultssupporting
confidence: 89%
“…Using these values, for example, we can estimate the vacancy density in bulk layers as 10 10 cm -3 , which is in good agreement with recent experiments [4]. These formation energies in inner bulk layers mainly originate from the elastic energy loss produced by the insertion of foreign atoms in bulk crystal structure [5]. It is noted here that the formation energy decreases as the point defect approach the interface.…”
Section: Resultssupporting
confidence: 89%
“…1(a). [13][14][15][16] The slab is made of (3-4)-monolayer (3-4 ML) metal atoms and 16 ML α-quartz SiO 2 , where the back surface of SiO 2 is terminated by hydrogen (H) atoms and thus the unit cell has one diffusing metal atom, 36-48 metal layer atoms, and 64 Si, 120 O, and 8 H atoms. A vacuum of 20 Å thickness is inserted between adjusting slabs.…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
“…All atom positions are optimized to produce the interface structure except the 2 ML SiO 2 and H of the back surface; thus the metal layers are slightly strained. [13][14][15][16] The reliability of the present unit-cell size was checked by changing the film thickness perpendicular to the interface. In addition, to check the cell size (area) along the interface, we calculate the chemical potential energies of the metal atom when the metal atom is located deep in the present SiO 2 film, i.e., away from the interface, and in the 3×3×3 SiO 2 bulk and found that the energy difference between them is less than 0.2 eV for the atoms considered here, which is the typical magnitude of the calculation error in this work.…”
Section: Calculation Model and Methodsmentioning
confidence: 99%
See 2 more Smart Citations